BUSINESS INFRASTRUCTURES – INSTRUMENTS FOR THE INITIATION OF BUSINESS COOPERATION - MATICIUC MĂDĂLINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
This paper aims at contributing to the understanding of the business infrastructure terminology, presenting the general concepts regarding the business infrastructures. Even if all around the world there are an increasing number of business incubators, industrial parks, science parks and clusters, there is a shortage of accumulated knowledge about all these business infrastructures. The originality of the paper is given by the idea of investigating the differences and similarities between the cluster infrastructures. We made an initial research on business infrastructures seen as a business model for increased performance of the small and medium enterprises. After the analysis of the business literature we observed that there is no systematic framework to understand these infrastructures and there is a lack of clarity regarding the terminology.